PENGEMBANGAN COOKIES MOUBE BERBASIS UBI JALAR UNGU DAN TEPUNG MOCAF UNTUK PENDERITA DIABETES MELITUS TIPE 2 - Gumilar, Mulus; Rahmat, Mamat; Fitria, Mona; Amanah, Ninda Risti (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
Currently, cases of Diabetes Mellitus (DM) in the world and in Indonesia are increasing. Based on the 2018 Riskesdas results, the prevalence of diabetes sufferers is 2%. This shows an increase in the prevalence of diabetes from 2013, namely 1.5%. Cookies are one of the food products that are starting to be developed as a snack for people with DM, besides that cookies are liked by various age groups and have a high shelf life. Modified cookies with Mocaf Flour and Purple Sweet Potatoes can be given as snacks to accompany DM products. Mocaf flour and purple sweet potato are foods with a low glycemic index so they are good for DM sufferers. Apart from that, purple sweet potatoes also contain antioxidants which can ward off free radicals to prevent oxidative stress. The aim of this research was to determine the effect of the formulation of Purple Sweet Potato and Mocaf Flour on the quality of Moube Cookies which meet dietary requirements and organoleptic properties. The research design used was an experiment with 30 trained panelists. The results of research on the organoleptic properties of the three formulas concluded that there were no significant differences with p (0.001) > α (0.05)..   Keywords: Diabetes Mellitus, Mocaf Flour, Purple Sweet Potatoes